Heading towards a better world. Part 2: the current world situation and the responsibility of universities. Issue 9 (20th October 2016) - Ernst, Richard R.
Abstract : The independence of academic teachers gives them the liberty to freely and honestly express their views in the hope of influencing the long-term societal development. Scientific explorations of the foundations of nature are important for gaining further knowledge to address urgent issues of our common future. But, in addition, academics are obliged to develop wisdom for comprehending the transdisciplinary and transcultural connections that are the clues for solving major pending problems. An overarching view may help us to conceive innovative societal models and to find possible avenues that will lead toward long-term prosperity and human dignity for all citizens on our globe, also in a distant future.